The Combination of High Calcium Milk with Citrus maxima Peels Ethanolic Extract Increased Bone Density of Ovariectomized Rats - Ragil S. Dianingati; Annisa Novarina; Amanita K. Hana; Laeli Muntafi'ah; Endang Lukitaningsih (Indonesian Society for Cancer Chemoprevention, 2015)
Osteoporosis is a common problem in menopause woman. The main cause is lack of estrogen hormone. Commonly, prevention therapy is by consuming high calcium milk, but it is not effective. Bali orange’s peel (Citrus maxima Merr.) is a waste material but known contains phytoestrogen according to previous study. Considering of this result, fortification of high calcium milk and Bali orange’s peel is expected to be an effective solution for osteoporosis in menopause woman. This research began with extraction of Bali orange’s peel (BPE) using ethanol 70% by maceration method. Ovariectomized Sprague Dawley female rats as the model of post menopausal woman were treated by BPE for 28 days. The doses of BPE was given to rats is 500 and 1000 mg/KgBW combined with high calcium milk. Bone density was determined using digital microradiography, the profile showed the increase of bone density in group that treated with combination of BPE 1000 mg/Kg BW and high calcium milk compare to control and given only milk groups. Docking molecular showed that BPE’s active compound which are hesperidin and naringin have interaction with estrogen receptor α and β. Docking score of naringin with ER α and β are -19,97; -18,99 respectively. Meanwhile the docking score of hesperidin with ER α and β are -19,98; +49,92 respectively. Overall, the result of this research showed that fortification of BPE with high calcium milk has good prospect to develop as effective therapy of osteoporosis.Keywords : Citrus maxima Merr., phytoestrogen, osteoporosis, high calcium milk, estrogen receptor